MO483CHA2DS2-VASC SCORE IN PATIENTS WITH EGFR<30 ML/MIN/1.73 M2 AND ATRIAL FIBRILLATION*. (29th May 2021) - Freese Ballegaard, Ellen Linnea; Bjerring Olesen, Jonas; Kamper, Anne Lise; Feldt-Rasmussen, Bo; Gislason, Gunnar; Torp-Pedersen, Christian; Carlson, Nicholas
Abstract: Background and Aims: CHA2 DS2 -VASc score (congestive heart failure, hypertension, age ≥75 years, diabetes mellitus, stroke or transient ischemic attack, vascular disease, age 65-74 years, female sex) is a validated tool for evaluation of risk of stroke and systemic emboli in patients with atrial fibrillation without nephropathy. The validity of risk determination based on the CHA2 DS2 -VASc score in patients with severe nephropathy is untested. We investigate the validity of the CHA2 DS2 -VASc score in patients with eGFR<30 ml/min/1.73m 2 (including dialysis treated patients) and atrial fibrillation without anticoagulation treatment. Method: In a retrospective cohort study, all patients with atrial fibrillation and eGFR<30 ml/min/1.73 m 2 were identified in nationwide Danish registers between 2008 and 2018 with subsequent exclusion of patients initiating anticoagulation treatment based on redeemed prescriptions. Cumulative incidences of stroke stratified on CHA2 DS2 -VASc score were computed using the Aalen-Johansen estimator, and one-year risk of stroke was calculated with comparison of CHA2 DS2 -VASc score based on Cox regression models adjusted for age, sex and dialysis status with G-computation of one-year risk standardized to the distribution of risk factors in the sample. Results: From 2, 452 patients with eGFR <30 ml/min/1.73 m 2 and de novo atrial fibrillation, a total of 1, 575 patients (64.2%) without anticoagulation treatment were included. Mean age was 78.0 years (standard deviation ±12.2), 53.3% were male, and 25.5% were on dialysis. The distribution of patients into CHA2 DS2 -VASc score categories of 0-1, 2, 3, 4 and ≥5 was 8.7%, 14.5%, 24.6%, 24.7% and 27.5%, respectively. Cumulative incidence of stroke in non-dialysis dependent and dialysis-dependent patients are shown in the figure . Overall, standardized one-year risk of stroke was 3.3% (95%CI 1.3-6.4%), 2.5% (95%CI 1.0-4.1%), 5.9% (95%CI 3.9-8.2%), 5.1% (95%CI 3.6-7.0%), and 7.3% (95%CI 5.2-10.2%) for CHA2 DS2 -VASc score categories of 0-1, 2, 3, 4 and ≥5, respectively. Comparably, standardized one-year risk of stroke was 2.5% (95%CI 0.3-5.7%), 1.9% (95%CI 0.0-4.7%), 7.4% (95%CI 3.2-11.5%), 4.7% (95%CI 1.0-8.3%), and 16.5% (95%CI 7.9-27.2%) for CHA2 DS2 -VASc score categories of 0-1, 2, 3, 4 and ≥5, respectively, in dialysis-treated patients, and 4.3% (95%CI 1.0-10.3%), 2.9% (95%CI 1.1-4.9%), 5.5% (95%CI 3.5-8.1%), 5.1% (95%CI 3.4-7.1%), and 5.9% (95%CI 3.8-8.5%) for CHA2 DS2 -VASc score categories of 0-1, 2, 3, 4 and ≥5, respectively, in non-dialysis-dependent patients. Conclusion: Overall, CHA2 DS2 -VASc score was associated with a progressive increase in one-year risk of stroke. Although the association was most obvious in non-dialysis dependent patients, discrepancy was evident with regard to risk in patients with CHA2 DS2 -VASc score ≤1 in both subgroups, albeit less so in adjusted analyses.